Transfer of Training as a Mediator of the Effect of Knowledge Characteristics on Nurses’ Performance - Bero Utomo; Dirga Lestari AS; Ariesta Heksarini (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The performance of nurses as professionals who are at the forefront of health services has an important role in determining the quality of services, including mental health services. For this reason, it is necessary to improve competence on a continuous basis. However, the knowledge gained by nurses during training has not been fully applied in work practice consistently. The purpose of this study is to analyze the role of transfer of training in mediating the influence of knowledge characteristics on the performance of nurses at the Atma Husada Mahakam Regional Psychiatric Hospital. This study uses a quantitative approach with an explanatory design to test the causal relationship between variables. The sample of this study is clinical nurses who directly provide services to patients, with sampling techniques using the purposive sampling method. The data collection method was carried out using a structured questionnaire that had been tested for validity and reliability. Data analysis using SEM-PLS The results showed that knowledge characteristics had a positive and significant effect on the transfer of training and nurse performance, but the transfer of training did not have a significant effect on nurse performance, so it was not able to mediate the relationship between knowledge characteristics and performance. These findings suggest that the improvement in nurse performance is more directly influenced by knowledge characteristics than through the process of transferring training results. The study highlights strengthening knowledge characteristics to improve nurse performance and improving training supervision and evaluation for effective training transfer.